2020
DOI: 10.1038/s41598-020-58109-0
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metallopeptidase expression and modulation by transforming growth factor-β1 in equine endometrosis

Abstract: Equine endometrial fibrosis (endometrosis) is described as a degenerative chronic condition in the uterus. Its characteristic feature is excessive deposition of extracellular matrix (ECM) components around the endometrial glands and stroma. Although matrix metallopeptidases (MMPs) that mediate ECM turnover are important factors in the process of fibrosis, knowledge of their expression and regulation in endometrosis is limited. In other species, one of the important regulators of MMPs and tissue inhibitors of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
1
16
0
4
Order By: Relevance
“…It has also been suggested that, in pulmonary fibrosis, MMP-9 is linked to inflammatory-induced tissue remodeling, while MMP-2 may be associated with impaired tissue remodeling, leading to abnormal collagen deposition and interstitial fibrosis [18]. Our studies showed that the endometrial expression of MMPs and their tissue inhibitors (TIMPs) is altered at the different stages of endometrosis, and in response to interleukins [19,20].…”
Section: Introductionsupporting
confidence: 54%
“…It has also been suggested that, in pulmonary fibrosis, MMP-9 is linked to inflammatory-induced tissue remodeling, while MMP-2 may be associated with impaired tissue remodeling, leading to abnormal collagen deposition and interstitial fibrosis [18]. Our studies showed that the endometrial expression of MMPs and their tissue inhibitors (TIMPs) is altered at the different stages of endometrosis, and in response to interleukins [19,20].…”
Section: Introductionsupporting
confidence: 54%
“…In equine explants, MMP-2 and MMP-9 secretion differed when challenged with cytokines and is dependent on the severity of endometrosis, which may link them to modifications in the endometrium that predispose to fibrosis development [ 37 ]. It was demonstrated that TGFβ1 treatment increased MMP-9 secretion in mare endometrial fibroblasts and epithelial cells and that the endometrial MMP expression changes at different categories of endometrosis [ 38 ]. In other tissues, the concomitant increased levels of MPO and MMP-2/-9 were also reported in rat temporomandibular joint inflammation [ 63 ], in inflamed human dental pulp tissue [ 64 ], and in fat meal induced endothelial damage in humans [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, MMP-2 transcription [ 35 ] and its active form [ 36 ] were up-regulated in mare endometrosis. Our latest in vitro studies in equine endometrium revealed that the expression of MMPs is altered by factors involved in inflammation [transforming growth factor (TGF) β1, interleukins and prostaglandins] [ 37 , 38 , 39 ], and could contribute to the fibrotic response to elastase [ 20 ] and cathepsin G [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endometrosis is defined as active or inactive fibrosis around the endometrial glands and in the stroma that is often associated with pathological changes in the endometrial glands within fibrotic foci [146,147]. Equine endometrosis causes alterations in endometrial function manifested by changes in its histology, ultimately leading to changes in the uterine microenvironment, ovarian cycle, and early pregnancy dysfunction [148][149][150]. Endometrial fibrosis is a serious problem in horse reproduction and poses a great economic loss to the horse-breeding industry.…”
Section: Endometrosismentioning
confidence: 99%